The Precarious State of Academic Freedom in Higher Education: The Case of India and Pakistan - Anand, Kusha (Research in the social scientific study of religion, 2022)
Academic freedom is increasingly under assault from authoritarian governments worldwide, supported by right-wing student groups who act as provocateurs within. Academic freedom is the freedom of academics to conduct critical enquiry, and the freedom of academics and students to collectively deliberate on any idea without fear of sanction, censure, or illegitimate interference. Yet, this right that is crucial for the pursuit of knowledge has witnessed widespread attacks in higher education institutions across India and Pakistan. The period since 2014, when the Bharatiya Janata Party (BJP) came to power under Prime Minister Narendra Modi, has seen an unprecedented assault on academic freedom and on academics. The recent penal measures taken against faculty members of the universities in India are analysed against this backdrop. On the other hand, higher education in Pakistan has suffered from a continuous lack of academic freedom, perpetuated by an increasingly non-secular environment and corresponding discriminatory policies by the government and educational institutions. The situation has been exacerbated by a ban on student unions in public universities and curbs on freedom of speech in universities resulting in student protests in the shape of student solidarity march and the resultant backlash by the government. This chapter thus examines the historical and current institutional policies and political discourse that has influenced academic freedom and the resultant backlash and activism by students in India and Pakistan.